Macroprudential Policy on Sharia Banking Financing: The Indonesian Experience - Cahyono, Eko Fajar; Rani, Lina Nugraha (Shirkah: Journal of Economics and Business, 2018)
The locus of macroprudential policy persuading banks has recently attracted significant attention for such research. Whether and to what extent macroprudential policies established by Bank Indonesia against sharia banks have not researched yet in previous empirical studies. Gathering data during 2008-2016, this article examines the impact of macroprudential policy on credit risk-taking by sharia banks in Indonesia. This research approach uses dynamic panel data analysis technique to investigate the relationship between risk-taking of sharia bank credit and macroprudential policy for a bank in Indonesia good sharia banking. This research shows that there is the influence of Bank Indonesia's macroprudential policy toward murabaha financing in Indonesia.  Keywords: macroprudential policy, credit risk, sharia bank